2021
DOI: 10.1007/s00428-021-03068-8
|View full text |Cite
|
Sign up to set email alerts
|

Molecular pathology of thymomas: implications for diagnosis and therapy

Abstract: Thymomas exhibit a unique genomic landscape, comprising the lowest on average total mutational burden among adult human cancers; a unique point mutation in the GTF2I gene in WHO type A and AB thymomas (and rarely others); almost unique KMT2A-MAML2 translocations in rare WHO type B2 and B3 thymomas; a unique YAP1-MAML2 translocation in almost all metaplastic thymomas; and unique miRNA profiles in relation to GTF2I mutational status and WHO histotypes. While most thymomas can be diagnosed solely on the basis of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 71 publications
(120 reference statements)
0
22
0
1
Order By: Relevance
“…Due to the differential expression of metabolites in TETs versus normal thymi (Figure 1), pathways related to proline, cysteine, glutathione, lactate and glutamine appear as potential therapeutic targets in refractory TETs, in which targeted treatments have remained elusive [71].…”
Section: Therapeutic Perspectivesmentioning
confidence: 99%
“…Due to the differential expression of metabolites in TETs versus normal thymi (Figure 1), pathways related to proline, cysteine, glutathione, lactate and glutamine appear as potential therapeutic targets in refractory TETs, in which targeted treatments have remained elusive [71].…”
Section: Therapeutic Perspectivesmentioning
confidence: 99%
“…Selbst bei beträchtlicher Größe können Thymome symptomfrei bleiben. Tumorbiologisch bestehen 2 seltene und wichtige Charakteristika: die einmalige Häufigkeit von fast 50 % paraneoplastischer Autoimmunphänomene und die Art der Metastasierung mit der Neigung von B2-und B3-Thymomen zu pleuraler Aussaat[30,31,32].…”
unclassified
“…A recent study has demonstrated common loss-of-function in TP53 in type B thymomas and TCs. 30 In a study by Peric et al ., two variants with stop codon have been identified R213* and V91*, as well as four pathogenic missense changes namely, D281N, G244S, R158C, E221K. 22 , 31 , 32 One of the newest studies by Xu S et al ., included in our meta-analysis, has analyzed the genomic profile of TETs that has indicated TP53 as the most mutated gene especially in both B3 and C thymoma causing worse prognosis.…”
Section: Discussionmentioning
confidence: 97%